Application of a JEG-3 organoid model to study HLA-G function in the trophoblast - Zhuang, Bai-Mei; Cao, Dan-Dan; Liu, Xiao-Feng; Wang, Li; Lin, Xiao-Li; Duan, Yong-Gang; Lee, Cheuk-Lun; Chiu, Philip C. N.; Yeung, William S. B.; Yao, Yuan-Qing (Frontiers in Immunology, 2023)
Abstract: The human placenta is a unique temporary organ with a mysterious immune tolerance. The formation of trophoblast organoids has advanced the study of placental development. HLA-G is uniquely expressed in extravillous trophoblast (EVT) and has been linked to placental disorders. With prior experimental methodology, the role of HLA-G on trophoblast function beyond immunomodulation is still contested, much less its role during trophoblast differentiation. Organoid models incorporating CRISPR/Cas9 technology were used to examine the role of HLA-G in trophoblast function and differentiation. JEG-3 trophoblast organoids (JEG-3-ORGs) were established with high expression of trophoblast representative markers and the capacity to differentiate into EVT. CRISPR/Cas9 based on HLA-G knockout (KO) significantly altered trophoblast immunomodulatory effect on natural killer cell’s cytotoxicity as well as trophoblast regulatory on HUVEC angiogenesis, but had no effect on the proliferation, invasion of JEG-3 cells and the formation of TB-ORGs. RNA-sequencing analysis further demonstrated that JEG-3 KO cells followed the similar biological pathways as their wild-type counterparts during the formation of TB-ORGs. In addition, neither HLA-G KO nor the exogenous addition of HLA-G protein during EVT differentiation from JEG-3-ORGs altered the temporal expression of the known EVT marker genes. Based on the JEG-3 KO (disruption of exons 2 and 3) cell line and the TB-ORGs model, it was determined that HLA-G has a negligible effect on trophoblast invasion and differentiation. Despite this, JEG-3-ORG remains a valuable model for studying trophoblast differentiation.